Hubungan Rinitis Alergi Dengan Rinosinusitis Kronik - Zhafran Ramadhan Lumbantobing; Mukhlis Imanto (Medula, 2021)
Chronic rhinosinusitis is an inflammatory and infectious disease of the paranasal sinuses with the characteristics of 5 major symptoms that have occurred for at least 12 weeks: nasal congestion, pain or pressure on the face, nasal obstruction, the presence of secretions in the nose anterior and posterior, and loss of smell. Allergic rhinitis is the most common predisposing factor for chronic rhinosinusitis because it is associated with obstruction of sinus ostium due to mucosal edema. As many as 50% - 84% of patients with chronic rhinosinusitis have a history of atopy to dust, fungi and allergies to animal hair and an increase in serum specific IgE antibodies and peripheral eosinophils associated with the onset of symptoms of chronic rhinosinusitis. In chronic rhinosinusitis patients with allergic rhinitis, hypersensitivity reaction occur and an increase in the number of inflammatory mediators such as histamine, proinflammatory cytokines such as interleukins, TNF-α (tumor necrosis factor), GM-CSF (granulocyte-macrophage colony stimulating factor) is more in the nasal mucosa compared with chronic rhinosinusitis patients without allergic rhinitis. All these inflammatory mediators will then lead to increased vascular permeability and hypersecretion of the mucus glands. The inflammatory process caused by allergic rhinitis will cause blockage of the ostiomeatal complex, impaired mucocilliary clearance, and impaired ciliary function resulting in paranasal sinus obstruction which will lead to chronic rhinosinusitis. It is very important for patients with allergic rhinitis to be managed properly both pharmacologically and non-pharmacologically in order to help prevent the occurrence of chronic rhinosinusitis.